Assessing the Financial Stability of Indian and Chinese Banking Sectors: A Comparative Study - Thomas, Robin (International Journal of Psychosocial Rehabilitation, 2019)
The purpose of this study is to compare the financial stability of the banking systems in India and China over a 20-year period from 2000 to 2019, and more specifically, over a 10-year period from 2010 to 2019. The comparison is conducted using statistical and graphical analysis of financial stability ratios such as NPAs to total loans, capital to total assets, regulatory capital to risk-weighted assets, Z-score, and provisions of non-performing assets. To measure the overall stability of the banking systems in both countries, a composite index was also constructed. The results reveal that while India still faces challenges with higher NPAs compared to China, both countries continue to struggle with maintaining financial stability in their banking systems. By identifying trends and patterns in the financial stability of the banking sectors in both countries, this study aims to provide valuable insights into the strengths and weaknesses of the banking sectors in India and China, which may aid in identifying areas for improvement.